1983
DOI: 10.1056/nejm198302103080602
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-Host Disease and Survival in Patients with Aplastic Anemia Treated by Marrow Grafts from HLA-Identical Siblings

Abstract: One hundred thirty patients with severe aplastic anemia were conditioned with cyclophosphamide for transplantation of marrow from HLA-identical siblings. The patients were selected for the present analysis according to the criterion of sustained marrow engraftment. Of the 130 patients, 97 are now alive between 1.4 and 11 years (median, 5) after transplantation. Twenty-nine of the thirty-three who died had either acute or chronic graft-versus-host disease (GVHD). Our analysis was directed at identifying factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
157
0
2

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(164 citation statements)
references
References 24 publications
5
157
0
2
Order By: Relevance
“…31,32 A clinical study showed that patients treated in laminar air flow rooms were less likely to develop GVHD than those treated in regular hospital rooms. 33 Because of the lower risk of GVHD in the home care group, TRM was also significantly lower in this group than in the controls (Figure 3, Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 81%
“…31,32 A clinical study showed that patients treated in laminar air flow rooms were less likely to develop GVHD than those treated in regular hospital rooms. 33 Because of the lower risk of GVHD in the home care group, TRM was also significantly lower in this group than in the controls (Figure 3, Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 81%
“…This was consistent with previous studies showing comparable risks of acute GVHD in patients with aplastic anemia, of whom some did and some did not receive infusions of viable donor buffy coat cells in addition to marrow grafts after conditioning with cyclophosphamide. 21 Also, several studies reported similar incidences of acute GVHD after G-PBMC and marrow grafts despite the infusion of 1 to 2 logs more CD3 þ cells in the G-PBMC inocula. 22,23 Perhaps, as suggested by Kernan et al, 24 once an initial threshold (10 5 CD3 þ cells/kg) of transplanted CD3 þ cells has been exceeded, further increases in T-cell numbers do not necessarily translate into more acute GVHD for given degrees of genetic disparity between donors and recipients.…”
Section: Discussionmentioning
confidence: 91%
“…These results were in agreement with previous observations in unrelated graft recipients after myeloablative conditioning, 25 but contrasted with findings in related ablative 26,27 and nonablative 28 recipients that showed a positive correlation between numbers of CD34 þ cells and incidence of chronic extensive GVHD, and also the finding of a higher incidence of chronic GVHD in patients with aplastic anemia given donor buffy coat cells in addition to related marrow grafts. 21 The reasons for the differences among related and unrelated recipients are unclear. Perhaps, greater disparity for minor histocompatibility antigens in the unrelated setting could lead to more chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…GVHD have already been associated with an inferior survival elsewhere. 18 The association of BuCy with a worst survival might be related to a toxic effect of busulfan on the microenvironment. 19 Cell dose is important for engraftment and survival after allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%